From Structure to Sensing: Molecular Mechanistic Insights into Plant-Derived Carbon Dots for Heavy Metal Ion Detection - Himanshi Soni; Vicky Jain; Suhas Ballal; Indang Ariati Ariffin; Mamata Chahar; Suman Saini; Monika Bhattu; Harbinder Singh; Mikhael Bechelany; Jagpreet Singh (Nanomaterials)
Plant-derived carbon dots (P-CDs) are gaining attention in environmental remediation due to their cost-effectiveness, availability, and lower toxicity compared with chemically synthesized carbon dots. This review comprehensively examines the recent advancements in the synthesis and application of P-CDs, with a particular emphasis on their efficacy in the sensing of heavy metals, which are among the most pervasive environmental contaminants. A detailed comparative analysis is presented by evaluating the performance of P-CDs against their chemically synthesized counterparts based on key parameters, such as optimal operating conditions and detection limits. Furthermore, sensing the potential of P-CDs towards every heavy metal ion has been discussed with in-depth mechanistic insights. Additionally, this review explores the industrial applications and future directions of P-CDs. This review provides a comprehensive analysis of -P-CDs for heavy metal sensing, aiming to enhance their sensitivity and selectivity toward heavy metal ions.